(untitled) (Geologica Macedonica, 2015)
Landslides are one of the most damaging and most significant geo-hazards in the Republic ofMacedonia. Due to many reasons landslide data collection in the past have been generally unsystematic. Knowingthat new occurrences are to be expected in future, brief overview on landslide databases in Europe is given and modelfor establishing and operation of national GIS landslide database is proposed in the paper. Model for assignment ofgovernmental body on landslides, along with structure and way of operation of the envisaged database is presented.Formation of this landslide database is the basic step towards better understanding of the landslide hazard in future.This database will enable conditions for selection of most endangered regions and selection of appropriate models forlandslide hazard and risk zonation. As a result, land use planning will become more efficient, and vulnerability ofpeople and goods will be decreased. In this context, some results from recent landslide susceptibility assessment studiesare also presented.